Genetic parameter estimates and principal component analysis of breeding values of reproduction and growth traits in female Canchim cattle - Buzanskas, M. E. [UNESP]; Savegnago, R. P. [UNESP]; Grossi, D. A.; Venturini, G. C. [UNESP]; Queiroz, S. A. [UNESP]; Silva, L. O C; Júnior, R. A. A. Torres; Munari, D. P. [UNESP]; Alencar, M. M. (CSIRO Publishing, 2013)
Phenotypic data from female Canchim beef cattle were used to obtain estimates of genetic parameters for reproduction and growth traits using a linear animal mixed model. In addition, relationships among animal estimated breeding values (EBVs) for these traits were explored using principal component analysis. The traits studied in female Canchim cattle were age at first calving (AFC), age at second calving (ASC), calving interval (CI), and bodyweight at 420 days of age (BW420). The heritability estimates for AFC, ASC, CI and BW420 were 0.03±0.01, 0.07±0.01, 0.06±0.02, and 0.24±0.02, respectively. The genetic correlations for AFC with ASC, AFC with CI, AFC with BW420, ASC with CI, ASC with BW420, and CI with BW420 were 0.87±0.07, 0.23±0.02, -0.15±0.01, 0.67±0.13, -0.07±0.13, and 0.02±0.14, respectively. Standardised EBVs for AFC, ASC and CI exhibited a high association with the first principal component, whereas the standardised EBV for BW420 was closely associated with the second principal component. The heritability estimates for AFC, ASC and CI suggest that these traits would respond slowly to selection. However, selection response could be enhanced by constructing selection indices based on the principal components. © CSIRO 2013.
Keywords: age at first calving; bodyweight; calving interval; selection index; breeding; cattle; female; genetic correlation; genetic parameters; heritability; nonhuman; principal component analysis; progeny; reproduction